2023
DOI: 10.1039/d2sc05197d
|View full text |Cite
|
Sign up to set email alerts
|

Xanthate-supported photo-iniferter (XPI)-RAFT polymerization: facile and rapid access to complex macromolecules

Abstract: Xanthate-supported photo-iniferter (XPI)-reversible addition-fragmentation chain-transfer (RAFT) polymerization is introduced as a fast and versatile photo-polymerization strategy. Small amounts of xanthate are added to conventional RAFT polymerizations to act as a...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 56 publications
(77 reference statements)
0
20
0
Order By: Relevance
“…This circumvented the reduction process of CTA precursors and a mismatch of quality in the R‐group. [ 50 ] Figure 5b and Figure S8 show that the ln([M] 0 /[M] t ) increases linearly with time, indicating the pseudo‐first‐order kinetics of the polymerization reaction. During the polymerization, the experimental number‐average molecular weight ( M n,exp ) obtained from GPC data increased linearly with BA conversion and Ɖ remained below 1.2 (Figure 5c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This circumvented the reduction process of CTA precursors and a mismatch of quality in the R‐group. [ 50 ] Figure 5b and Figure S8 show that the ln([M] 0 /[M] t ) increases linearly with time, indicating the pseudo‐first‐order kinetics of the polymerization reaction. During the polymerization, the experimental number‐average molecular weight ( M n,exp ) obtained from GPC data increased linearly with BA conversion and Ɖ remained below 1.2 (Figure 5c).…”
Section: Resultsmentioning
confidence: 99%
“…This circumvented the reduction process of CTA precursors and a mismatch of quality in the R-group. [50] Figure 5b and Figure S8 show that the ln([M] 0 /[M] t ) increases linearly with time, indicating the pseudo-Figure 5 (a) Mechano-RAFT polymerization of BA with ZnO-1 catalyst under US; (b) semilogarithmic kinetic plots of evolution and (c) monomer conversion versus number average molecular weight (Mn) and molecular weight distribution (Ɖ); (d) monomer conversion versus Mn,theo, and Mn,exp between this work and our previous work. [43] Comprehensive Report Ding et al first-order kinetics of the polymerization reaction.…”
Section: Resultsmentioning
confidence: 99%
“…34-36, 42, 47 The method has a further advantage for the present study: it can be performed at ambient temperature, which is an important prerequisite for the PLA substrate (Tg ≈ 57°C) 48 used for 3D-printing. As xanthates are a particularly active type of CTA for such a process [49][50][51] O-ethyl-2-propionic acid xanthate (Xan) was used. The carboxylate functionality was later used as an anchor group to be coupled to amino groups present on functional surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…26 Li et al 27 suggested that the tolerance was caused by the fact that some oxygen was consumed on the radicals formed from the CTA after photolysis. Lehnen et al 28 also observed some oxygen tolerance in xanthate-supported photoiniferter polymerization (which was absent when stirring), noting that the process that removed oxygen from solution during irradiation also degraded CTA. In addition, most of the works reporting oxygen tolerance used DMSO as a solvent, indicating a relationship between oxygen tolerance and DMSO.…”
Section: Introductionmentioning
confidence: 99%